Kenya - Implementation Manual : Financing Mechanisms for Solar Electric Equipment - World Bank (Washington, DC, 2014)
This manual is based on more than two year's worth of field experience in Kenya during which about 120 solar home systems (SHS) were installed through different financing mechanisms. It outlines two different finance approaches that address lighting and power needs of 1) rural households with regular cash income and 2) small businesses with the potential to increase their productivity with solar-powered electricity. This report found that it was feasible to establish financing mechanisms for solar electric systems for use in households and small businesses-once the right partners were identified and clear procedures were identified indicating each partner's responsibilities. The desire to have electricity is so deeply-rooted that households that have a chance to obtain loan to acquire a solar electric system will do so. In order to get these financing mechanisms off the ground, a certain amount of technical assistance for training and quality control is necessary, as is a limited financial assistance to slightly reduce the costs of the loans offered.